Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan (Studi Pada Pelanggan Emas UD. Enggal Kec. Pakisaji, Kab. Malang) - Pramudya, Arya Krisna (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
Service is one of the factors that need to be considered to win the competition tight. Service is an activity or outcome that can be offered by a company to another party that is usually invisible, and the results can not be owned by others. The existence of a good quality of service in a company would create satisfaction for its customers. UD. Enggal is one of the businesses engaged in trading gold . The existence of UD. Enggal basically a newcomer, but the monthly sales volume is always increasing. With keen competition UD condition . Enggal seeks to improve the quality of service to its customers. This study aims to determine the effect of simultaneous or partial service quality variables consisting of Physical Evidence, Reliability, Responsiveness, Collateral, and Empathy to the Customer Satisfaction , and to know the variable quality of service that is more dominant influence customer satisfaction. Keywords : service quality, customer satisfaction